The Relationship Between Anxiety Level and Mathematics Learning Achievement on the Area of Rectangles and Squares in Class IV Students - Putri Hendria; Zaka Hadikusuma Ramadan (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
This study aims to determine the relationship between anxiety levels and mathematics learning achievement regarding the area of rectangles and squares in class IV students at SDN 21 Pekanbaru. This type of research is quantitative with a correlation model. Data collection techniques used anxiety scales and written tests. The population in this study were all students at SDN 21 Pekanbaru and the sample used was class IV C students at SDN 21 Pekanbaru. Prerequisite tests use normality, linearity and heteroscedasticity tests. The data analysis technique used is Pearson product moment with the help of SPSS 25. The normality test results for the anxiety scale and learning achievement are 0.749 and 0.074, the value is greater than 0.05, so the data is normal, the linearity result is 0.511, which is greater than 0.05, so the data stated to be linear, and the heteroscedasticity test of 0.205 is greater than 0.05, it is concluded that there is no heteroscedasticity in the data. The Pearson product moment test result is 0.007 where the value is <0.05. There is a significant relationship between the anxiety variable and mathematics learning achievement, with the direction of the relationship being negative because the correlation coefficient results have a negative sign (-) which means, the higher the students' anxiety regarding mathematics learning, the lower the students' learning achievement results will be.